Cracking the Code: A Pronunciation Error Analysis of Tenth-Grade Students at SMK SMTI Bandar Lampung - Kholid, Idham; Irawansyah; Lestari, Putri (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This study analyzed pronunciation errors made by tenth-grade students at SMK SMTI Bandar Lampung during the first semester of the 2023/2024 academic year. The objectives of the research were to identify the pronunciation errors, particularly in monophthong sounds, and to determine the causes of these errors. The study employed a qualitative research methodology. The participants were tenth-grade students of SMK SMTI Bandar Lampung, with a sample of 30 students from the KI 2 class, selected using purposive sampling. Data collection involved students being given 36 words containing short and long monophthong vowel sounds (/ɑ:/, /ɪ:/, /u:/, /ɜ:/, /ɔ:/, /ɒ/, /ɪ/, /ʊ/, /e/, /æ/, /ʌ/, /ə/). The pronunciation errors were analyzed using the Linguistic Category Taxonomy, as proposed by Dulay. Additionally, observations were conducted to identify the causes of errors based on Brown’s theoretical framework. The findings revealed that students made a total of 923 pronunciation errors in monophthong sounds, comprising 473 errors in short vowels and 450 errors in long vowels. Common errors included replacing correct sounds with incorrect ones, adding unnecessary sounds, and omitting required sounds. Regarding the causes of errors, interlingual transfer was identified as the most frequent cause. Other contributing factors included intralingual transfer, the context of learning, and communication strategies